The Role of Throughput Accounting in Supporting the Requirements of Administrative Decisions: A Field Study in Industrial Companies in Iraq - حمه أمين عثمان عبد القادر; السالم مناضل عبدالجبار; صالح جليل ابراهيم (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
This research aims to know the role of applying throughput accounting (TA) and its role in supporting the requirements of administrative decisions, as well as to what extend it is possible to apply throughput accounting in the industrial environment reality in Iraq in general and the industrial companies operating in Iraq in particular. The study is based on three hypotheses which were tested by using the descriptive analytical method and a questionnaire to explore the perceptions of (110) sample respondents which included a number of employees of industrial companies operating in Iraq. The number of respondents who returned the questionnaire was (103). This amounts to (%92.63) which is considered an acceptable ratio. The questionnaires were analyzed using the statistical tool (SPSS). The study concluded with a number of results, that most important of which are: Throughput accounting is regarded as an integral tool and method rather than a competitive one in the industrial companies as throughput accounting seeks to reach to the optimum level of achievement, thus maximizing the profits of companies in the short term. The use of throughput accounting enables management to take decisions which lead to the use of limited resources more efficiently in the production processes in order to increase the achievement of the economic unit. Lack of awareness among workers in industrial companies about the importance and the concept of throughput accounting. There are problems and obstacles that limit the application of throughput accounting in the Iraqi industrial companies. In light of the results, the study made several recommendations, the most important of which is that it is imperative to apply and use throughput accounting in the Iraqi industrial companies in the light of the modern trends of management accounting .Accordingly industrial companies should increase their interest in using modern costing methods to measure the cost of production in order to rationalize administrative decisions by focusing on continuous improvement using the method of throughput accounting.